Drug development for mitochondrial disease: recent progress, current challenges, and future prospects. (2nd January 2016) - Bénit, Paule; Schiff, Manuel; Cwerman-Thibault, Hélène; Corral-Debrinski, Marisol; Rustin, Pierre
Abstract : Introduction : Since their recognition in the late 80s, mitochondrial diseases have been, and still are, essentially intractable. Despite the hope raised by gene therapy for a fraction of mitochondrial diseases, we still urgently need to devise efficient strategies to fight these multifaceted diseases. Areas covered : Here we discuss the reasons that might account for this situation and, in particular, emphasize the extreme variation of clinical presentations and/or of the disease course and consequences observed in affected patients. The broad impact of mitochondrial losses of function, increasingly recognized as instrumental in a number of cancers and degenerative diseases, makes the identification of targets and development of drugs an important and worthwhile endeavor over the coming years. With this aim, we need workable models for these diseases that reproduce the spectacular variability of these diseases in humans. Expert opinion : Among the challenges lying ahead, we need to design trials likely to simultaneously take into account (a) the rarity and (b) the variability of mitochondrial diseases, and (c) the predictable occurrence of responders and nonresponders to any potential therapy of these disorders.